2014
DOI: 10.1186/1472-6963-14-147
|View full text |Cite
|
Sign up to set email alerts
|

Rural area in a European country from a health care point of view: an adaption of the Rural Ranking Scale

Abstract: BackgroundIn many countries, rural areas are facing a shortage of general practitioners (GPs). Appropriate strategies to address this challenge are needed. From a health care delivery point of view, the term rural area is often poorly defined. However rural areas have to be adequately defined to ensure specific strategies are tailored to these environments. The aims of this study were to translate the New Zealand 6-item Rural Ranking Scale (RRS), to culturally adapt it and to implement it to identify rural are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 14 publications
1
12
0
2
Order By: Relevance
“…In general, studies have shown that GPs as well as other medical specialties tend to be located in urban areas [5, 6]. The data presented in our study revealed higher GP densities on city level: in our study the overall physician-to-population ratio (PPR) was 1:1550 (SD: 139.3).…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In general, studies have shown that GPs as well as other medical specialties tend to be located in urban areas [5, 6]. The data presented in our study revealed higher GP densities on city level: in our study the overall physician-to-population ratio (PPR) was 1:1550 (SD: 139.3).…”
Section: Discussionsupporting
confidence: 49%
“…This spatial distribution has been shown to depend on numerous socioeconomic and demographical factors: Large demographic studies identified a shortage of providers located in the countryside and a relative oversupply in metropolitan areas leading to a mismatch of demand and supply [5, 6]. Similar to the GP distribution (supply), population sizes (demand) vary geographically: people are migrating towards large urban centers to pursue job opportunities or further education [7].…”
Section: Introductionmentioning
confidence: 99%
“…[21]. In anderen Untersuchungen wurde festgestellt, dass Ärzte, die auf dem Land aufgewachsen sind, sich dort eher niederlassen als Städter [19,22,23].…”
Section: Itemunclassified
“…Despite their poorer health status and greater health-related needs (Strasser, 2003;Bennett , Olatosi and Probst, 2008), residents of rural and remote sett ings have limited access to health services (Goodridge and Marciniuk, 2016), healthcare workforce (Steinhaeuser et al, 2014), and health information (Carlson et al, 2006;Smith, Humphreys and Wilson, 2008), especially in low and middle income countries such as Romania (Vlădescu et al, 2016). In this context, when facing health risk situations, rural residents commonly rely on family networks and friends for support and advice (Wathen and Harris, 2007).…”
Section: Introductionmentioning
confidence: 99%